Carcinogenesis and lung cancer: 70 years of progress and more to come. (3rd September 2020) - Samet, Jonathan M
Abstract: This commentary celebrates the 40th year of Carcinogenesis, spanning 1980–2020 with a focus on lung cancer. For lung cancer, these 40 years come toward the end of a century of scientific inquiry that began with descriptions of this highly fatal malignancy and that closes with emphasis on molecular processes and genomics. This commentary gives a historical perspective of lung cancer research as well as a look into the questions that remain to be addressed. Over the 20th century and into the first two decades of the 21st, a series of issues have more or less sequentially been the focus of epidemiological investigation of lung cancer, as questions have been answered and methodologies have evolved. These questions began with whether an epidemic was occurring and continue now with exploration of causal mechanisms and molecular risk predictors. With tobacco smoking firmly established decades ago as a cause of lung cancer, the evidence has long been sufficient to motivate tobacco prevention and control. There is unfinished business as tobacco smoking remains widespread and the industry continues to market new, addicting, products.